FinTech innovation : from robo-advisors to goal based investing and gamification - Sironi, Paolo (Chichester, West Sussex, United Kingdom : Wiley, 2016)
A survival guide for the FinTech era of banking FinTech Innovation examines the rise of financial technology and its growing impact on the global banking industry. Wealth managers are standing at the epicenter of a tectonic shift, as the balance of power between offering and demand undergoes a dramatic upheaval. Regulators are pushing toward a'constrained offering' norm while private clients and independent advisors demand a more proactive role; practitioners need examine this banking evolution in detail to understand the mechanisms at work. This book presents analysis of the current shift and offers clear insight into what happens when established economic interests collide with social transformation. Business models are changing in profound ways, and the impact reaches further than many expect; the democratization of banking is revolutionizing the wealth management industry toward more efficient and client-centric advisory processes, and keeping pace with these changes has become a survival skill for financial advisors around the world. Social media, big data analytics and digital technology are disrupting the banking industry, which many have taken for granted as set in stone. This book shatters that assumption by illustrating the massive changes already underway, and provides thought leader insight into the changes yet to come. -Examine the depth and breadth of financial technology -Learn how regulations are driving changing business models -Discover why investors may become the price-makers -Understand the forces at work behind the rise of FinTech Information asymmetry has dominated the banking industry for centuries, keeping the banknvestor liability neatly aligned-but this is changing, and understanding and preparing for the repercussions must be a top priority for wealth managers everywhere. Financial Innovation shows you where the bar is being re-set and gives you the insight you need to keep up.
6.2 Foundations of Goal Based Investing6.3 About Personal Needs, Goals, and Risks; 6.4 Goal Based Investing Process; 6.5 What Changes in Portfolio Modelling; 6.6 Personal Values; 6.7 Goal Elicitation; 6.8 Goal Priority; 6.9 Time Horizons; 6.10 Risk Tolerance; 6.11 Reporting Goal-Centric Performance; 6.12 Conclusions; Chapter 7: The Investment Journey: From Model Asset Allocations to Goal Based Operational Portfolios; 7.1 Introduction; 7.2 Main Traits of Modern Portfolio Theory; 7.3 Main Traits of Black-Litterman; 7.4 Mean-Variance and Mental Accounts.
7.5 Main Traits of Probabilistic Scenario Optimization.
Includes bibliographical references and index.
Print version record.
Keywords: Financial services industry -- Technological innovations; Finance -- Technological innovations; Financial engineering; Electronic books